Changing trends in the evaluation of ejection fraction in patients hospitalized with acute myocardial infarction: The Worcester Heart Attack Study - Santolucito, Paul A. (2008)
BACKGROUND: Extent of left ventricular dysfunction in patients with acute myocardial infarction (AMI) is an important predictor of subsequent morbidity and mortality. It is unclear, however, how often ejection fraction (EF) findings are evaluated in the setting of AMI, and the characteristics of patients who do not have their EF evaluated, particularly from the more generalizable perspective of a population-based investigation. PURPOSE: The purpose of this study was to examine nearly 3 decade long trends (1975-2003) in the evaluation of EF in patients admitted with confirmed AMI (n=12,760) to all greater Worcester (MA) hospitals during 14 annual periods. RESULTS: The percentage of patients undergoing evaluation of EF prior to hospital discharge increased substantially between 1975 (4%) and 2003 (73%). Despite these encouraging trends, approximately one quarter of patients in our most recent study year did not receive an EF evaluation. In the mid-1970's through mid-1980's, radionuclide ventriculography was typically used to assess EF whereas echocardiography was most often used to evaluate EF during more recent periods. Predictors of not undergoing an evaluation of their cardiac function included older age, shorter length of hospital stay, code status limitations, dying during hospitalization, Medicare insurance, several comorbidities, and a recent non-Q-wave MI. CONCLUSIONS: The results of this community-wide study suggest that a considerable proportion of patients with AMI fail to have their EF evaluated. Efforts remain needed to optimize the use of cardiac imaging studies and link the results of these studies to improved patient outcomes.